Review Article: Impact of Growth Hormone Treatment on Height in Children with X-Linked Hypophosphatemic Rickets - Al-Zubaidi , Munib A.; Abdullah, Wasnaa H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: X-linked hypophosphatemic rickets (XLHR) is the most frequent form of inherited rickets. In children, stunted growth and disproportionately short stature are frequently the early signs of XLHR.Objective: To review different opinions in the review of literature about the use of growth hormone in the treatment of XLHR.Methods: This review article followed a systematic literature review approach, there areno exclusion criteria.Main Findings: Growth retardation may continue even after receiving appropriate conventional treatment (phosphate supplements and active analogs of vitamin D) in XLHR, even if it is initiated early in childhood. Recently, regardless of a well-controlled disease, treatment with recombinant human growth hormone (rhGH) was suggested as an effective way of supporting growth in children with XLHR exhibiting a lack of growth. It is necessary to follow until reaching adult height to assess the long-term effects of rhGH treatment on the ultimate height.Conclusion: The addition of rhGH to optimal medical treatment might represent a promising option in the significant portion of affected patients with XLHR and growth failure. Follow-up is needed until the final height is reached to evaluate the long-term benefit of rhGH treatment on final height. Further studies will be necessary to determine the most efficient treatment protocol concerning doses, duration, and age of initiation or rhGH in short children with XLHR. However, further studies would be needed to study the addition of rhGH to optimal medical treatment in short children with XLHR.